(untitled) (PANGEEA, 2025)
In the private area, the pandemic has had the greatest impact on social distancing, with communication being rarer and the fear of contracting the disease having a negative impact on their lives. From the analysis of the interviews, it is quite clear what the preference of the way of working is and what impact work life has had on personal life and how much this has been influenced. Based on the results we can state that the preferences for the mode of work tend to be more for the remote mode as it has more benefits from the employees’ perspective. Looking at the pandemic effects felt in the work sector, as well as in the family setting, we found out from the respondents that for the professional sphere the effects were some positive ones, helping them to be more focused and productive, not having the possibility to perform other activities. Of course there were also less desirable effects due to the pandemic. The lack of socialisation was felt by all respondents. Some even spent more time with their families than before and this brought them closer together. On the other hand, a little distance was felt on the side of relationships with loved ones or friends, communicating only online. The fact that in some families there were also children, there the personal sphere was affected more: once in a positive sense, especially in the first part of the isolation, when they spent more time together, communicated and interacted more with their children, but then the isolation was felt in a negative way, especially children missing the presence and play with their friends from school or kindergarten, but also going out to parks or not participating in other activities that consume their energy and keep them busy so that parents can carry out their professional activities in the remote version.